Too complex to digest? Federal tax bills and their processing in US financial markets - Hamza Bennani; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2022)
In this paper, we analyze whether the complexity of tax bills affects financial markets. Based on the Flesch-Kincaid grade level of the 32 tax bills identified by Romer and Romer (2010) in the period 1962-2003, we assess the relationship between tax bills' complexity and financial markets using an event study approach. Our results show a negative (positive) and significant relationship between the present value of tax bills and changes in the 10-year government bond yields (S&P 500 returns). The magnitude of this relationship increases over time, suggesting that market participants underreact at first and need a couple of days to digest the information contained in the tax bills. This delay can be explained by the textual characteristics of the bills in the case of the 10-year yields as a lower readability partly offsets the negative relationship for up to three days after the signing of a tax bill, but not thereafter. In the case of the stock market, we find similar offsetting evidence, but only for a part of the readability measures employed in this paper.
Keywords: G14; H20; H30; 330; Complexity; Event Study; Financial Markets; Readability; Tax Bills